A contrarreforma agrária no Brasil: análise da expulsão de camponeses dos assentamentos rurais da Paraíba - Costa Júnior, Clodoaldo Brandão (2022)
The insufficient role of the Brazilian State in structuring and making feasible rural land reform settlement projects that are capable of providing adequate conditions for the reproduction of settled peasants has historically cast some members of this social class into a situation of intentional deprivation that forces them to leave the land they have conquered. As a result, evasions in rural settlement projects are recurrent. In Paraíba, official data point to a 21% evasion rate, leading many settlements to fail to even reach and maintain the maximum capacity of families possible to be settled. A significant part of these settlers who drop out have spent years and years in camps for the struggle for land, deprived of adequate living conditions, and anxiously awaiting to be made effective as settlers, there being no desire in them to leave the land after joining the National Program of Agrarian Reform. For that reason, this thesis sought to contribute to the debate by bringing the concept of "expulsion of rural peasants from the settlements", for understanding that part of this process of evasion from the settlements is a symptomatic response, and not a casual one, to an unfavorable burden thrown upon the settled peasant who, lacking options, leaves the lot even in the face of his desire to remain on the land. This expulsion is generated by the disregard for the settled peasant, the delay in structuring actions, the difficulty in accessing credit, the complexity of becoming productively effective, the breaking of deadlines for forming settlements according to plans previously drawn up by INCRA, the rupture of expectations nurtured by the settlers, the constant threat of losing the land, among other mishaps that buffet the settled family to the point where the desire to remain is overtaken by the need to leave, thus being expelled. Thus, this thesis represents an effort to analyze the correlation between the process of expulsion of settled peasants from settlements in Paraiba and the agrarian counter-reform policy adopted in Brazil by the different federal governments, from the period of entry into the Military Regime to the removal of Dilma Rousseff from the presidency, evaluating the State as the main agent of this process. For this, the research is anchored in the theoretical conceptions of the contradictory, unequal and combined process of development of capitalism; of agrarian counter-reform; of the territory of hope; besides, of course, of the expulsion of peasant settlers. In its construction, ample documental and bibliographical research was carried out, and the fieldwork was concentrated in the settlements of Paraíba José Antônio Eufrouzino (Campina Grande), Serra do Monte (Cabaceiras) and Calabouço (Araruna); it was developed through participant research, making use of oral interviews, photographic records and field notebook. This work identified enough elements to understand as true the hypothesis that the Brazilian State, intentionally and historically, promotes a policy of agrarian counter-reform that has culminated in problematic settlements and with difficulties in retaining their settlers, producing the expulsion of peasants from rural settlements in Paraíba.